The Prime Ministers who Never Were : A Collection of Political Counterfactuals - Edited By Becket, Francis (London Biteback, 2011)
Each of these chapters in this book of political counterfactuals describes a premiership that never happened, but might easily have done had the chips fallen slightly differently. The contributors, each of them experts in political history, have asked themselves questions like: what shape would the welfare state and the cold war have taken if the Prime Minister had been Herbert Morrison instead of Clement Attlee? What would have been consequences for Northern Ireland had Norman Tebbit succeeded Margaret Thatcher? How would our present life be different without New Labour - a name we would neve.
Keywords: Politics and government